Embedded Wids Kismet Sebagai Perangkat Deteksi Serangan Data Link Layer Wi-Fi Access Point - Fachrurozy, Rizky; Setiadji, Muhammad Yusuf Bambang; Priambodo, Dimas Febriyan (Jurnal Informatika: Jurnal Pengembangan IT, 2023)
The rapid development of wireless network technology has an impact with a significant increase of users. Wi-Fi is one of the wireless technologies that is currently used widely by humans as a medium of transmission to exchange information. The increasing in the number of users is directly proportional to the increase the risk of crime occurring. In this case an attack on a Wi-Fi network aimed at taking certain advantage of the user or it’s victim was done by threatening aspects of information security. Wireless Intrusion Detection System (WIDS) is a tool used to detect intrusions that occur against wireless network technology, one of it is Wi-Fi into the form of logs. Kismet is one of the wids that is free and opensource with complete WiFi attack detection capability. The implementation of WIDS Kismet applied to Raspberry Pi 4 was shown as an alternative wids device that has a low cost for use in small Wi-Fi network environments such as home networks or small enterprise. The analysis is done by calculating the performance of accuracy, precision, recall, and f-measure values from the implementation results using confusion matrix method. The result of the calculation obtained by the highest value for each calculated performance with 99.83% accuracy, 97.96% precision, 100% recall, and 98.9% fmeasure. The calculation aims to provide information that can be utilized for users who want to do a similar implementation and use it to detect Wi-Fi networks.